Prevalence of Pitiriasis Versicolor in Taman Aries Settlement RT 001/RW 006, West Jakarta - Monica Puspa Sari; Inneke Kusumawati Susanto; Benny Effendi Wiryadi; Chadijah Latief; Reinaldo Putra Hardian (Fakultas Kedokteran dan Ilmu Kesehatan Ukrida, 2023)
Pityriasis Versicolor or commonly known as panu is a superficial fungal infection on the skin which is caused by Malassezia furfur and can be identified with hypopigmentation or hyperpigmentation macula, smooth squama and itchy-sensation. Pityriasis Versicolor commonly infects face, neck, trunk, upper arm, armpit region, thigh, and fold of the skin. This infection infects especially in male at mature age with high activity and lack of personal hygiene. The purpose of the experiment is to discover the description of prevalence of pityriasis versicolor in residential area Taman Aries RT 001, RW 006, Jakarta Barat in regards to the general description, sex, age, education, and occupation. An experiment is conducted with cross-sectional method in December 2016 in residential area Taman Aries RT 001/ RW 006, Jakarta Barat. Researcher asks the participants to fill the informed consent and questionnaire, then does the physical examination to find hypopigmentaton lesions on the skin. Skin scraping is done on the lesion. The skin scrapes will be given KOH 10% and examined under the microscope to find the evidence of Malassezia furfur. From 93 participants, 13 participants is found with hypopigmentation lesion on the skin and proven to be positive on microscopic examination with KOH 10%. The prevalence of pityriasis versicolor in residential area Taman Aries RT 001/ RW 006, Jakarta Barat is 14,0%. The cause is an improvement in life style, economy, and personal hygiene.